Pathogen Enzyme-Mediated Alkoxyamine Homolysis as a Killing Mechanism of Aspergillus fumigatus - Marion Filliâtre; Pierre Voisin; Seda Seren; Ines Kelkoul; Olivier Glehen; Philippe Mellet; Sophie Thétiot-Laurent; Jean Menotti; Sylvain R. A. Marque; Gérard Audran; Abderrazzak Bentaher (Journal of Fungi, 2025)
The emergence of antifungal-resistant Aspergillus fumigatus (A. fumigatus) became a serious public health concern, underscoring the need for new effective antifungal agents. Here, we present a strategy based on the in situ generation of radical species that are toxic to the pathogen. The synthesis of an alkoxyamine linked to a peptide substrate recognized by A. fumigatus-secreted dipeptidyl peptidase is described. Kinetic experiments show a stable prodrug prior to enzymatic activation. Ensuing peptide cleavage and spontaneous homolysis resulted in the generation of a stable nitroxide and a reactive alkyl radical moiety. Next, the exposure of A. fumigatus spores to the prodrug lead to pathogen growth inhibition in a compound concentration-dependent fashion (e.g., 42% inhibition at 10 µg/L). Importantly, the designed alkoxyamine inhibited not only the growth of a clinical voriconazole-susceptible A. fumigatus strain, but also the growth of a strain resistant to this azole. To determine the antifungal importance of the reactive alkyl radical, its substitution with a non-radical structure did not prevent A. fumigatus growth. Furthermore, the introduction of succinic group in the peptide substrate resulted in the loss of alkoxyamine antifungal properties. Our work reports a novel chemical strategy for antifungal therapy against A. fumigatus based on the pathogen enzyme-mediated generation of toxic radicals. Significantly, these findings are timely since they could overcome the emerged resistance to conventional drugs that are known to target defined pathogen biologic mechanisms such as ergosterol synthesis.